2017
DOI: 10.1016/j.agwat.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Global synthesis of drought effects on cereal, legume, tuber and root crops production: A review

Abstract: As a result of climate change, drought is predicted to pose greater pressure on food production system than in the past. At the same time, crop yield co-varies with both environmental (e.g., water, temperature, aridity) and agronomic variables (i.e., crop species, soil texture, phenological phase).To improve our quantitative understanding on the effect of these co-varying factors on agricultural productivity, we synthesized previous meta-analysis studies summarizing the results of numerous independent field ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
159
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(168 citation statements)
references
References 101 publications
6
159
0
3
Order By: Relevance
“…Averaged over six years of field experiments [43], and despite its larger yield potential, T. durum produced 25%-30% less grain yield than T. aestivum; whereas, grain yield, in accordance with earlier reports [20], was reduced by 28 and 23%, respectively due to PS II when compared to PS I. Although T. durum has better water and nutrients use efficiencies under high-yielding environments and it tolerates abiotic stress better than T. aestivum, it has lower grain yield than T. aestivum under low-yielding environments [21,40]; however, both wheat genotypes responded similarly to changes in abiotic stresses in this and other studies [20]. It was speculated [72] that the constitutively larger kernel weight in T. durum is associated with its lower fruiting efficiency when compared with T. aestivum; nevertheless, kernels m −2 in both genotypes was the most sensitive yield component to abiotic stress in this and other studies [39,73], presumably due to its larger plasticity and high heritability (Table 2).…”
Section: Wheat Genotypessupporting
confidence: 78%
See 1 more Smart Citation
“…Averaged over six years of field experiments [43], and despite its larger yield potential, T. durum produced 25%-30% less grain yield than T. aestivum; whereas, grain yield, in accordance with earlier reports [20], was reduced by 28 and 23%, respectively due to PS II when compared to PS I. Although T. durum has better water and nutrients use efficiencies under high-yielding environments and it tolerates abiotic stress better than T. aestivum, it has lower grain yield than T. aestivum under low-yielding environments [21,40]; however, both wheat genotypes responded similarly to changes in abiotic stresses in this and other studies [20]. It was speculated [72] that the constitutively larger kernel weight in T. durum is associated with its lower fruiting efficiency when compared with T. aestivum; nevertheless, kernels m −2 in both genotypes was the most sensitive yield component to abiotic stress in this and other studies [39,73], presumably due to its larger plasticity and high heritability (Table 2).…”
Section: Wheat Genotypessupporting
confidence: 78%
“…Differences in PPs between the wheat genotypes are likely linked to the level of agronomic and genetic improvement that they underwent [21]. Stress phases caused a shift in frequency distributions of PPs, deviation from normality, and skewness in a few traits, and exposed many differences between the wheat genotypes in their reaction to abiotic stresses during both stress phases (Figure 1).…”
Section: Inter-and Intraspecific Variation In Ppsmentioning
confidence: 99%
“…Drought‐induced decrease in RD may be associated with the greater embolism, leading to higher RM (Chapin et al, ; Chaves, ; Roumet et al, ). We also found that the responses of RL and SRL to drought differed significantly among plant functional groups (Figure ), which may be attributed to the difference in strategies of different groups to obtain nutrients and water to support their growth in response to drought stress (Daryanto, Wang, & Jacinthe, ). For example, herbs may have stronger C‐use efficiency than woody plants under low drought intensity because thinner RD of herbs may benefit plants to enhance the ability to leverage photosynthetic C by reducing reliance on mycorrhizae (Ma et al, ).…”
Section: Discussionmentioning
confidence: 84%
“…Increased R/S is a plant avoidance mechanism in response to drought when drought increases the proportion of RB relative to aboveground biomass (Hermans, Hammond, White, & Verbruggen, 2006;Hodge, 2009;Zhou et al, 2017). Meanwhile, the response of R/S to drought varied among plant functional types ( Figure 6), which might be attributed to the different strategies of plant functional types to obtain water and nutrients and distribution of RB at different soil profile (Daryanto et al, 2017). For example, more C can be easily allocated into roots in response to drought due to thinner RD in herbs than woody plants (Ma et al, 2018).…”
Section: Drought-induced Changes In Rb and Its Relationships With Mmentioning
confidence: 99%
“…Many previous studies have evaluated the impacts of drought on crop yields for rainfed (e.g., Popova et al, ; Potopová et al, ) and irrigated (e.g., Daryanto et al, , ; Sweet et al, ; Trnka et al, ) systems. This has also extended into the economic impacts of drought using market prices and production functions at the basin scale (e.g., Kirby et al, ), input‐output analysis (e.g., Pérez y Pérez & Barreiro‐Hurle, ), Ricardian cross‐sectional analysis of net revenues, and computable general equilibrium models to capture economy‐wide and global‐scale changes of climate change (Mendelsohn & Dinar, ).…”
Section: Introductionmentioning
confidence: 99%